Screening mental health risks for adolescents in South Korea - Euntaek Hong; Joohee Lee; Seowon Yoon; Surin Cho; Yong-Chun Bahk; Yong-Chun Bahk; Jeongwon Choi; Kee-Hong Choi; Kee-Hong Choi (Frontiers in Psychology, 2025)
BackgroundDepression, anxiety, and suicidal ideation are significant mental health problems among adolescents, especially in South Korea, which has one of the highest adolescent suicide rates globally. However, few standardized and validated mental health screening tools exist for this population. This study aimed to examine the psychometric properties and establish normative data for the Mental Health Screening Tool for Depressive Disorder (MHS: D), Generalized Anxiety Disorder (MHS: A), and Suicide Risk (MHS: S) in South Korean adolescents.MethodsAn online survey involving 6,689 students and out-of-school youths (aged 10–18 years) was conducted between July and August 2021. Psychometric properties—including reliability, validity, and measurement invariance—were assessed by comparing adolescent and adult samples and demographic subgroups within the adolescent sample.ResultsAll three screening tools demonstrated excellent internal consistency (Cronbach’s α: MHS: D = 0.92, MHS: A = 0.93, and MHS: S = 0.86) and adequate unidimensional factor structure in the adolescent sample. A multi-group confirmatory factor analysis showed that the unidimensional factor structure of each instrument was maintained between the adolescent and adult samples, and that measurement invariance was maintained across adolescent sex and age subgroups. Reference norms indicated higher symptom prevalence among girls compared to boys, with symptom severity increasing with age. Significant correlations with mental health indicators (i.e., somatization, self-harm, perceived stress, and peritraumatic COVID-19 stress) supported the high construct validity of the instruments and highlighted the detrimental impact of mental health concerns on overall well-being.ConclusionThe MHS: D, MHS: A, and MHS: S demonstrated excellent psychometric properties across sex and age subgroups in a representative adolescent sample. Using these validated tools in clinical and community settings can aid in monitoring adolescent mental health and preventing suicide risk.